MENGKAJI (BUDAYA) SANAD ULAMA TANAH JAWA - Fathurrahman Karyadi (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2013)
This article discusses the alumni of Japan Indonesian Muslimviewpoints in connection with their study experiences in Japan. Theirmotivations to study in Japan are opportunity available, the ease of getting a scholarship, boost the positive image of Japanese from their parents, positive impression on Japan from their senior, interest in Japanese culture and technology advances, interest in English-language classes and programs. The constraints they face while studying in Japan is divided into academic and nonacademic issues. Academic problems are: different fields of study with academic tutors, language and communication problems, the problem of interaction with academic counselors. Non-academic problems did not largerly happen becausethey did not experience financial problems, obtaining economicalaccommodation for academic tutors help, having special facilities for foreign students, can overcome the problem by cooking own food, buy food at the halal food store or order via the internet, able to adapt to different weather and climate, and social support from the community and the government of Japan that helps international students so that they feel comfortable studying in Japan.Keywords: Muslim, Indonesia, study, Japan